2017
DOI: 10.1016/j.ophtha.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab Injection as Primary Treatment in Patients with Retinopathy of Prematurity

Abstract: Intravitreal injection of ranibizumab seemed to be effective in treating patients with ROP. After treatment, there were primarily 3 different outcomes. Our predictive tree model is helpful for ophthalmologists to evaluate the risk of reactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 32 publications
3
54
4
2
Order By: Relevance
“…Our inclusion criteria are broader than the screening guideline recommendations in the USA (GA <30 weeks, BW <1500 g) and UK (GA <32 weeks, BW <1500 g)1 22 because severe ROP occurs in more mature and larger infants in China 23 24. The mean PMA for the time of first IVC is 34.2±1.9 weeks and 5.8±1.4 weeks, which is in accordance with 36.6±3.2 PMA by Wu et al and 36.0±2.34 PMA by Huang et al in the study of bevacizumab and ranibizumab treatment for infants with ROP, respectively,25 but slightly earlier than the 38.47±2.72 weeks reported by Jin et al 26. We found that using an IVC injection once, as monotherapy, resulted in the regression of plus disease without recurrence in 83.7% (40/48) of eyes with type 1 ROP and AP-ROP.…”
Section: Discussionsupporting
confidence: 88%
“…Our inclusion criteria are broader than the screening guideline recommendations in the USA (GA <30 weeks, BW <1500 g) and UK (GA <32 weeks, BW <1500 g)1 22 because severe ROP occurs in more mature and larger infants in China 23 24. The mean PMA for the time of first IVC is 34.2±1.9 weeks and 5.8±1.4 weeks, which is in accordance with 36.6±3.2 PMA by Wu et al and 36.0±2.34 PMA by Huang et al in the study of bevacizumab and ranibizumab treatment for infants with ROP, respectively,25 but slightly earlier than the 38.47±2.72 weeks reported by Jin et al 26. We found that using an IVC injection once, as monotherapy, resulted in the regression of plus disease without recurrence in 83.7% (40/48) of eyes with type 1 ROP and AP-ROP.…”
Section: Discussionsupporting
confidence: 88%
“…The difference was significant only for ROP located in retina Zone I (the most posterior region of the retina). (4) This study was followed by several case series, (5)(6)(7) small trials (8)(9)(10) and two small dosing studies. (11,12) In clinical practice, anti-VEGF agents are increasingly being used worldwide to treat ROP.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in our study, the 39 eyes from the 21 patients whose PMA at the first IVR injection was ≤35.4 weeks also did not progress to retinal detachment. However, Zhao et al [ 16 ] reported that retinal detachment occurred in 5 of the 49 eyes (10.2%) with APROP in patients given the first IVR injection at a mean PMA of 37.3 ± 5.2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshihiro et al reported that infants who were injected at an older PMA progressed to tract retinal detachment more quickly [ 17 ]. A single burst of VEGF contributes to neovascularization during the ROP process [ 18 ], and late IVR treatment during the period when the VEGF levels are decreasing may induce fibrosis and contraction of flat neovascularization peripherally to cause tight detachment [ 16 , 17 ]. Our study showed high proportions of APROP patients with older PMAs, because our hospital is a tertiary referral center in Beijing, and we receive patients with severe ROP from all parts of the country.…”
Section: Discussionmentioning
confidence: 99%